Regulation of macrophage activation by lactylation in lung disease - Wei, Yungeng; Guo, Hua; Chen, Shixing; Tang, Xiao Xiao (Frontiers in Immunology, 2024)
Lactylation is a process where lactate, a cellular metabolism byproduct, is added to proteins, altering their functions. In the realm of macrophage activation, lactylation impacts inflammatory response and immune regulation. Understanding the effects of lactylation on macrophage activation is vital in lung diseases, as abnormal activation and function are pivotal in conditions like pneumonia, pulmonary fibrosis, COPD, and lung cancer. This review explores the concept of lactylation, its regulation of macrophage activation, and recent research progress in lung diseases. It offers new insights into lung disease pathogenesis and potential therapeutic targets.